2021
DOI: 10.7554/elife.60960
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between the chloroplast protein import and SUMO systems revealed through genetic and molecular investigation in Arabidopsis

Abstract: The chloroplast proteome contains thousands of different proteins that are encoded by the nuclear genome. These proteins are imported into the chloroplast via the action of the TOC translocase and associated downstream systems. Our recent work has revealed that the stability of the TOC complex is dynamically regulated by the ubiquitin-dependent chloroplast-associated protein degradation (CHLORAD) pathway. Here, we demonstrate that the TOC complex is also regulated by the SUMO system. Arabidopsis mutants repres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…The rapid decomposition of TOC complexes mediated by chloroplastassociated protein degradation (CHLORAD) has been reported for the decrease in the transportation efficiency of chloroplast preproteins under stress conditions (Ling et al, 2012(Ling et al, , 2019. Two recent works showed the function of SUMOylation in the regulation of the TOC components: SUMOylation partially protects TOC159 from UPS-mediated degradation under a low gibberellic acid condition during early development (Accossato et al, 2020); SUMOylation components regulate the CLORAD pathway to coordinate the destruction of the TOC complex (Watson et al, 2021). However, the functions of SUMO conjugations on chloroplast preproteins are completely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rapid decomposition of TOC complexes mediated by chloroplastassociated protein degradation (CHLORAD) has been reported for the decrease in the transportation efficiency of chloroplast preproteins under stress conditions (Ling et al, 2012(Ling et al, , 2019. Two recent works showed the function of SUMOylation in the regulation of the TOC components: SUMOylation partially protects TOC159 from UPS-mediated degradation under a low gibberellic acid condition during early development (Accossato et al, 2020); SUMOylation components regulate the CLORAD pathway to coordinate the destruction of the TOC complex (Watson et al, 2021). However, the functions of SUMO conjugations on chloroplast preproteins are completely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, SUMOylation directly improves the importation efficiency of chloroplast preproteins to maintain the function of chloroplasts under HS, possibly antagonizing the impact of the excessive degradation of TOC. Given that the stability of TOC components is also modulated by SUMOylation (Accossato et al ., 2020; Watson et al ., 2021), it will be interesting to dissertate the balance mechanism of chloroplast protein importation mediated via the cooperation of SUMOylation on preproteins and TOC components under HS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent analysis has shown that Toc159 SUMOylation protects Toc159 from UPS-dependent degradation prior to TOC assembly [ 91 ]. On the other hand, like the sp1 mutants, Arabidopsis mutants for a number of components in the SUMO pathway including SUMO2 and SUMO3 can partially suppress the phenotypes of the ppi1 mutant for Toc33 through improving chloroplast development and enhancing accumulation of key Toc proteins [ 92 ]. Therefore, the SUMO system can both stabilize and destabilize key Toc proteins, probably dependent on different biological contexts.…”
Section: Chloroplast-associated Protein Degradation (Chlorad)mentioning
confidence: 99%
“…Furthermore, the interaction between AtHSC70-4 and AtCHIP is not under the precondition that AtCHIP ubiquitinates AtHSC70-4, but is predicated on the basis that AtHSC70-4 and AtCHIP together mediate plastid precursor degradation (Lee et al, 2009 ). Therefore, the interaction between AtHSC70-4 and AtSCE1 mediates plastid precursor SUMOylation (Watson et al, 2021 ). There are multiple examples of Ub-protein ligases interacting with the same substrate, including anaphase-promoting complex AtAPC11, AtPUB59, and AtPUB60 interacting with AtPRP8B and AtJMJ24, AtPUB59, and AtPUB60 binding a nuclear matrix protein-like protein complex THOC (AtTHO1 and AtTHO3) and more.…”
Section: The Regulation Of As Through Ptmsmentioning
confidence: 99%